The complexity of mucosal damage in gastroesophageal airway reflux disease: A molecular perspective - Sheng Chen; Min Wang; Shuai Zhang; Xin Huang; Xinke Sui; Dou Li; Changqing Zhong; Wei Wu (Gastroenterology & Endoscopy)
Gastroesophageal airway reflux disease (GARD) refers to a class of diseases in which the contents of the digestive system reflux into esophagus, the upper and lower airways, mouth, ear and nose et al., causing uncomfortable symptoms. It covers gastroesophageal reflux disease and extra-esophageal reflux disease. GARD is one of the most common diseases in clinical practice. The main cause of GARD-related clinical symptoms and signs of GARD is the structural damage and functional disability, which were caused by repeated contact between the mucous epithelium of the reflux tract and the acidic and non-acidic components of the reflux. Over the years, major progress has been made in the understanding of the molecular pathogenesis of reflux associated mucosal inflammation, suggesting a complex and multifactorial pathogenesis and immune-mediated effects. Thus, we reviewed the clinical and pathophysiological characteristics of GARD and probe the complexity of the pathogenesis of GARD-related mucosal inflammation from the aspects of microscopic changes and specific molecular mediators. New drug therapies for the mucosal injuries in the reflux tract were also reviewed. From bench to bedside, these novel molecular findings might provide new perspectives and therapeutic approaches for GARD.